2011
DOI: 10.1186/1475-2891-10-65
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thinness in children and adolescents in the Seychelles: comparison of two international growth references

Abstract: BackgroundThinness in children and adolescents is largely under studied, a contrast with abundant literature on under-nutrition in infants and on overweight in children and adolescents. The aim of this study is to compare the prevalence of thinness using two recently developed growth references, among children and adolescents living in the Seychelles, an economically rapidly developing country in the African region.MethodsWeight and height were measured every year in all children of 4 grades (age range: 5 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
23
5
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 33 publications
(48 reference statements)
9
23
5
4
Order By: Relevance
“…The height and body weight rise markedly in children during their primary school years (ages 6-12) [25][26][27]. Body mass index (BMI) also substantially changes with age during childhood [28].…”
Section: Discussionmentioning
confidence: 99%
“…The height and body weight rise markedly in children during their primary school years (ages 6-12) [25][26][27]. Body mass index (BMI) also substantially changes with age during childhood [28].…”
Section: Discussionmentioning
confidence: 99%
“…Until 2007, when Cole et al (10) proposed international age-and sex-specific thinness cut-offs from 2 to 18 years to provide comparable prevalence rates of thinness, trends in thinness among children and adolescents had been seldom described (11) and the comparisons between countries had been difficult due to the use of several cut-off points (Centers for Disease Control and Prevention, WHO and International Obesity Task Force growth references) and different terms (underweight, wasting, thinness, undernutrition), which have a different meaning in adults, adolescents and children (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) . In their paper, Cole et al 'tried to avoid potential confusion between the terms wasting and underweight in children by adopting the term thinness, which WHO uses to mean low BMI in adults and adolescents' and 'extended the definition to include low BMI for age in children, linked to the adult definition through the fulcrum of BMI 17 at age 18'.…”
mentioning
confidence: 99%
“…If, on the one hand, the proportions of stature were significantly higher among boys, on the other hand, in the case of the proportions of excess of body weight, the girls showed significantly higher values. In other studies available in the literature important differences were also found between genders regarding the occurrence of stature and excess of body weight [13][14][15][16][17] . The differences observed in the proportions of stature deficit between boys and girls possibly can be explained due to the peculiarities observed regarding the biological sensitivity to environmental problems, especially of nutritional order.…”
Section: Resultsmentioning
confidence: 89%
“…Regard the values of body weight-for-height, the relative frequencies observed in the more elevated decile (17.7% of girls and 17.5% of boys) also approached two times more than the 10% expected, while in the lower decile, the relative frequencies observed did not outnumber the four percentages (3.3% of girls and 2.5% of boys) - Figure 1. Upon consulting the results of other studies, it was found that the greatest deficits in height and risk of overweight/obesity in young populations of regions in the process of development occur precisely at the time that precedes the beginning of the outbreak of maturityl [13][14][15][16][17] . This fact is explained based on the justification that, during this period of human development, there are significant changes related to physical growth, thus requiring proper and balanced provisions regarding short and long term to health, the purpose of the profile found in both nutritional indicators, highlights the importance of maintaining the actions aimed at the control of hunger and malnutrition in the population.…”
Section: Resultsmentioning
confidence: 99%